The Self in Question: A Comparative Study of Descartes’ Cogito and Buddhist Philosophical Views - Rahaman, MD Zizaur (Journal of Contemporary Buddhist Society = JCBS, 2025)
Descartes’ cogito affirms a permanent thinking self that is foundational to modern Western thought, emphasizing rational autonomy and dualism between mind and body. Conversely, Buddhism denies the existence of a permanent self, viewing identity as a transient aggregation of experiences. This perspective underlies a broader ethical framework promoting compassion and interconnectedness. By contrasting Descartes’ individualistic rationalism with Buddhist impermanence, the analysis explores how each tradition influences understandings of consciousness, morality, and human identity. While Descartes locates selfhood in rational thought, Buddhism challenges fixed identity constructs, advocating self-transcendence through meditation and ethical action.